Investigating a Participatory Intervention in Multidisciplinary Cancer Care Teams Using an Integrative Organizational Model: A Study Protocol - Chênevert, Denis; Brown, Tyler L.; Pomey, Marie-Pascale; Benomar, Nadia; Colombat, Philippe; Fouquereau, Evelyne; Loiselle, Carmen G. (Frontiers in Psychology, 2022)
Multidisciplinary teams encounter many challenges that can lead to higher levels of distress and burnout. This trend is acutely prevalent among multidisciplinary cancer care teams who frequently contend with increased task complexity and numbers of patients. Resilience is emerging as a critical resource that may optimize team members’ psychological health and wellbeing, work efficiency, and organizational agility, while reducing burnout. Accordingly, the proposed study aims to implement and evaluate a promising participatory interventional approach that fosters team resilience. Specifically, the effects of the intervention on participating team members will be compared to a control group of non-participating team members. This intervention’s core components include skills training, patient-centered meetings, talking spaces, and an agile problem-solving approach. The proposed study also seeks to determine whether enhanced resilience improves team mental health status and organizational outcomes. A participatory interventional approach will be implemented and assessed at three-time intervals (i.e., pre-intervention deployment [N = 375], 12 months post-deployment [N = 236], and 24 months post-deployment [N = 146]) across 5 cancer care teams in 3 Quebec healthcare institutions. A mixed methods design will be used that includes observations, semi-structured interviews, focus groups, and self-report questionnaires. Direct observation will document team functioning and structural resources (e.g., meetings, conflict management, leadership). Semi-structured interviews will explore participants’ experience with activities related to the participatory interventional approach, its perceived benefits and potential challenges. Focus groups will explore participants’ perceptions of their team’s resilience and the effectiveness of the intervention. Questionnaires will assess support, recognition, empowerment, organizational justice, individual, psychological safety, work climate, team resilience, workplace burnout, engagement, quality of work life, wellbeing, and organizational citizenship behaviors, and sociodemographic variables. Moreover, objective measures including absenteeism and staff turnover will be obtained via human resource records. Structural equation modeling will be used to test the study’s hypotheses. The proposed protocol and related findings will provide stakeholders with quantitative and qualitative data concerning a participatory interventional approach to optimize team effectiveness. It will also identify critical factors implicated in favorable organizational outcomes in connection with multidisciplinary cancer care teams. Expected results and future directions are also presented herein.